Early Life Pb Exposure and its Effect on Later Life Retinal Degeneration. Issue 10 (16th May 2017) - Modgil, Shweta; Cameotra, Swaranjit S.; Sharma, Vijay L.; Anand, Akshay
ABSTRACT: The study presents the longitudinal effect of early life lead exposure on retinal ischemia. Swiss albino mice were exposed to lead acetate at two different timepoints viz. postnatal day 1–20 and at 7th week of age. These mice were then followed till 10 week of age and subjected to retinal ischemia. Retinal ischemia was induced using pterygopalatine artery ligation. The effect of prior lead exposure on ischemic insult was determined using various histological and molecular parameters. Although toxic effects of Pb are well reported, but the results in this study showed not much significant effect of early life Pb exposure on later life retinal degeneration. While retinal thickness was decreased in surgery group and 7th week Pb exposed group, PND Pb exposed mice showed retinal thickness comparable to normal control. There was no difference in TUNEL positive cells in Pb exposed group when compared to surgery group. The molecular studies revealed overexpression of BDNF and GFAP in PND Pb exposed mice reflecting more injury and inflammation. The combined results revealed that Pb exposure have mild effect on overall susceptibility to retinal damage in later life. The Pb may exert its toxic effects at longer duration and thus the toxic effects may be mapped at longer timepoints. The study provides a new dimension to the already well known toxic effects of lead which needs to be further explored. J. Cell. Biochem. 118: 3213–3224, 2017. © 2017 Wiley Periodicals, Inc. Abstract : (i) Low dose Pb exposure during postnatal stages in mice have marginal adverse effect on damage caused by ischemia in later life. (ii) PND lead exposed mice showed better cell survival of Retinal ganglion cells as shown by TUNEL. (iii) PND lead exposed mice showed increased expression of neurotrophins and glial activation but exact mechanism remain to be explored.